NaFePO4 Cathode Prepared from The Caustic Fusion of A Mix Ilmenite-Hematite Followed by Cyclic Voltammetry for Na Insertion - Fitria Rahmawati; Dwi Aman Nur Romadhona; Syulfi Faiz (Chemistry Department, The University of Brawijaya, 2020)
Research to prepare NaFePO4 cathode material from iron sand was conducted. The iron sand consists of ilmenite FeTiO3 and hematite Fe2O3. A caustic fusion method used to precipitate iron as Fe(OH)3 and it increased Fe content up to 94.71 %. Phosphate precipitation successfully produced trigonal FePO4 and monoclinic FePO4 comply with ICSD#412736 and ICSD#281079. The prepared-FePO4 was then used as a precursor for Na insertion by applying cyclic voltammetry mode within 2.0 – 4.0 V with 0.05 mVs-1 of the scan rate. It produced orthorhombic olivine NaFePO4 and a secondary phase of orthorhombic Na0.7FePO4. Impedance analysis at 20 Hz – 5 MHz found that the material provided a semicircle at 100 Hz peak point, indicating electrode-bulk interface with a resistance value of 1735W, comparable to the electrical conductivity of 5.36 x 10-6 Scm-1. Even though the conductivity value is quite lower than NaFePO4 prepared from a commercial FePO4 that has been conducted in our previous research, however the electrical conductivity still reliable for cathode.